The Cajuns of East Texas - Louder, Dean; Leblanc, Michael (Cahiers de géographie du Québec, 1979)
Although French contacts with Texas go back 300 years, the first permanent mass settlement by francophones began at the turn of the twentieth century when a class of rural migrant workers spilled across the Sabine River from Louisiana settling the open prairies along the principal transportation routes between Beaumont and Houston. Shortly thereafter, the establishment of oil refineries in the Golden Triangle area attracted other Cajuns. Following a momentary pause during the depression years, migration picked up once again as numerous war related industries developed in the Port Arthur area. Today the primarily urban Cajun population of East Texas is less and less conscious of its ethnic differences with mainstream America. Three different associations have been formed to maintain and promote ethnic identity and the use of French.